Проблемні питання фінансової безпеки України та шляхи їх вирішення - Фещенко, Л. В.; Юкса, Т. М. (НТУ "ХПІ", 2014)
Визначено місце та роль фінансової безпеки в системі національної безпеки країни, розглянуто проблемні питання щодо стану фінансової безпеки України як складової економічної безпеки, визначено основні причини їх виникнення та загрози для економіки України. Досліджено рівень фінансової безпеки країни шляхом розрахунку спеціальних індикаторів. На основі результатів здійсненого аналізу запропоновано шляхи поліпшення незадовільного рівня кожної cкладової фінансової безпеки України.

There are been the place and the role of financial security in the country's national security, financial security is defined as an extremely complex multi-level system, which is formed by a number of subsystems, each of which has its own structure and logic of development., there are been considered problematic issues of financial security of Ukraine as a part of economic security, because finance is the foundation of any economy. Determine the cause and the greatest threats to the financial security of the state аnd proposed measures to improve its level. The level of financial security was investigated by calculating the indicators of financial security. On the basis of analysis propose solutions of unsatisfactory level of each component of financial security of Ukraine, developed the main ways to improve monetary and exchange rate policy in Ukraine, directions improve the formation of the budget system, improve the management of internal and external debt of the state.
Issues of financial security of Ukraine and ways their decision
Keywords: глобальна економічна система; національна безпека країни; економічна безпека; індикатори; economic security; financial security; indicators; level of financial security